Preparation-free resonator array atomic memory for on-chip quantum storage - Haechan An; Zongfeng Li; Mahdi Hosseini (APL Quantum, 2025)
We propose a light storage technique utilizing an array of photonic resonators that mimic atomic frequency comb memory. This method can be implemented on a solid-state photonic chip without requiring spectral hole burning. By eliminating the need for long preparation cycles and leveraging tunable photonic resonances, this approach offers high bandwidth, high efficiency, and a fast duty cycle simultaneously and without compromise.